2018
DOI: 10.1021/acsomega.8b02090
|View full text |Cite|
|
Sign up to set email alerts
|

Cisplatin-Loaded Graphene Oxide/Chitosan/Hydroxyapatite Composite as a Promising Tool for Osteosarcoma-Affected Bone Regeneration

Abstract: Presently, tissue engineering approaches have been focused toward finding new potential scaffolds with osteoconductivity on bone-disease-affected cells. This work focused on the cisplatin (CDDP)-loaded graphene oxide (GO)/hydroxyapatite (HAP)/chitosan (CS) composite for enhancing the growth of osteoblast cells and prevent the development of osteosarcoma cells. The prepared composites were characterized for the confirmation of composite formation using Fourier transform infrared spectroscopy, scanning electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 40 publications
3
42
0
Order By: Relevance
“…This is because the CS beads crosslinked at pH = 6.0 (TPP6) were completely ionic-crosslinking dominated and those beads crosslinked at pH = 9.0 (TPP9) were dominated by deprotonation accompanied with slightly ionic crosslinking, corroborating ATR-FTIR data, in agreement with other reports in the literature [35,37,45]. After the incorporation of HA into CS and CS/DEX beads (CS/HA-TPP9, CS/HA-TPP6, CS/HA/DEX-TPP9, and CS/HA/DEX-TPP6), the two main peaks at 2 value of 25.6° and 31.7° which are (002) and (211) reflections of HA, respectively [59][60][61][62], can be clearly seen in Figure 6. It can also be seen that the broad peak assigned to chitosan at 20.0° becomes wider and weaker with the incorporation of HA.…”
Section: Xrd Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…This is because the CS beads crosslinked at pH = 6.0 (TPP6) were completely ionic-crosslinking dominated and those beads crosslinked at pH = 9.0 (TPP9) were dominated by deprotonation accompanied with slightly ionic crosslinking, corroborating ATR-FTIR data, in agreement with other reports in the literature [35,37,45]. After the incorporation of HA into CS and CS/DEX beads (CS/HA-TPP9, CS/HA-TPP6, CS/HA/DEX-TPP9, and CS/HA/DEX-TPP6), the two main peaks at 2 value of 25.6° and 31.7° which are (002) and (211) reflections of HA, respectively [59][60][61][62], can be clearly seen in Figure 6. It can also be seen that the broad peak assigned to chitosan at 20.0° becomes wider and weaker with the incorporation of HA.…”
Section: Xrd Analysissupporting
confidence: 91%
“…According to release profiles, all beads presented a sustained release during the studied period (24 h), but the drug release rate was affected by the pH of the coagulation solution used in the preparation of the beads. The beads prepared at pH After the incorporation of HA into CS and CS/DEX beads (CS/HA-TPP9, CS/HA-TPP6, CS/HA/DEX-TPP9, and CS/HA/DEX-TPP6), the two main peaks at 2θ value of 25.6 • and 31.7 • which are (002) and (211) reflections of HA, respectively [59][60][61][62], can be clearly seen in Figure 6. It can also be seen that the broad peak assigned to chitosan at 20.0 • becomes wider and weaker with the incorporation of HA.…”
Section: In Vitro Drug Releasementioning
confidence: 99%
“…Wang et al reported collagen (Col)-mediated biomimetic synthesis of HA on GO support for the formation of bioactive Col/GO-HA composites, which exhibited improved hydrophilic and mechanical properties, as well as the ability to promote the bone repair by testing the osteoblastic cells [27]. Besides osteoblastic cells, other cells, such as MC3T3-E1, human mesenchymal stem cells, and osteosarcoma play important roles in the bone growth, repair, and regeneration [81,82,83,84,85]. For instance, Zhang and co-workers presented the biomineralization of HA crystals with a size of tens nm on 3D graphene foams (GFs) in 10× SBF containing 10 mM HCO 3 − ions [82].…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…In addition, biomimetic graphene-HA nanohybrids can be utilized as regeneration medicines for bone repair [83,86]. For instance, Sumathra et al reported a novel GO-HA based regeneration medicine tool for osteosarcoma-affected bone regeneration [83]. In their study, HA crystals were first biomineralized on GO surface and CS was then conjugated onto the formed GO/HA hybrids to create GO/HA/CS composites.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Craniomaxillofacial (CMF) bone damage, surgical, infection and bone disease can result in serious bone defects [1][2][3][4]. All of those bone defects brought the high burden to patients both on economic and spiritual [5,6].…”
Section: Introductionmentioning
confidence: 99%